Evaluation of EZH2 and ERRα in colorectal carcinoma: an immunohistochemical study - Abou Gabal, Hoda; Ahmed, Naglaa; Meckawy, Ghada; Yassin, Radwa; Hakim, Sarah (Polish Journal of Pathology, 2021)
The combined immunohistochemical evaluation of EZH2 (enhancer of zeste homolog 2) and ERRα (estrogen-related receptor α), in relation to clinicopathological prognostic factors and patients’ outcome, has not been performed yet in colorectal carcinoma (CRC). In order to achieve this aim, 120 samples were extracted; 60 cases of CRC; and 60 samples from normal colonic tissue. Our study showed that 63.3% and 38.3% of CRC cases reveal high EZH2 and high ERRα nuclear expression, respectively. 6.6% and 8.3% of normal colonic mucosa samples express low EZH2 and low ERRα nuclear expression, respectively. High EZH2 and high ERRα expression correlate with late tumor stages (p = 0.001 each), high grade (p = 0.001, p = 0.009 respectively), positive lymph node involvement (p = 0.001, p = 0.002 respectively) and larger tumor size (p = 0.001 each). There is a moderate highly statistically significant agreement (κ = 0.467, p = 0.001) between EZH2 and ERRα immunohistochemical expression. By Kaplan Meier analysis, high EZH2 and high ERRα show statistically significant shorter overall survival, and progression free survival than cases with low EZH2 and low ERRα immunohistochemical expression, respectively. Thus, EZH2 and ERRα might serve as potential promising prognostic markers in CRC.